Comparing and Modeling the Thermal Inactivation of Bacteriophages as Pathogenic Viruses Surrogates in Chicken Litter Compost. Issue 2 (2nd April 2020) - Wang, Hongye; Bridges, William; Chen, Zhao; Gong, Chao; Jiang, Xiuping
Abstract: The aim of this study was to compare and model the thermal inactivation of bacteriophages as surrogates for pathogenic viruses, such as avian influenza virus, in chicken litter compost. Three bacteriophages [ø6, MS2, and Felix O1 (FO)] were inoculated separately into aged chicken litter compost with various moisture contents (MCs), and then exposed to 75 and 85 °C for up to 3 h. The bacteriophage ø6 was undetectable during come-up time at all tested conditions. After 3 h heat treatment at 75 °C, population reductions of MS2 in the compost with 20, 30, and 40% MCs were 5.83, 6.08, and 8.32 log plaque forming units (PFU g −1 ), respectively, as compared with 4.87, 5.40, and 5.75 log PFU g −1 for FO, respectively. When exposed to 85 °C, population reductions of MS2 in the compost with 20, 30, and 40% MCs were 6.07, 7.93, and 8.03 log PFU g −1, respectively, as compared with 6.29, 6.20, and 7.59 log PFU g −1 for FO, respectively. Both bacteriophages MS2 and FO had higher recovery rates from compost, and bacteriophage MS2 had a comparable thermal resistance with the reported resistance of avian influenza virus than bacteriophage FO. Additionally, the proposed non-linear three-phase model was developed to describe the survival of bacteriophages exposed to the physical-heat treatment into different stages. Considering that virus may survive in some cold spots of compost piles, this study provides scientific evidence for the fertilizer industry to validate the effectiveness of their heating process in order to inactivate avian influenza virus in chicken litter compost.